Design of Vacuum-Induced Freezing Protocols for High Fill Volume Formulations in Freeze-Drying: A Strategic Approach - Wenzel, Tim; Gieseler, Margit; Gieseler, Henning (Journal of Pharmaceutical Sciences, 2020)
This case study proposes a development strategy for the SynchroFreeze vacuum-induced surface freezing technology for challenging high fill volume model systems. Critical steps during the development of a nucleation protocol are discussed as an example approach for implementing vacuum-induced surface freezing for high fill volume products. Slow pressure ramps and hold steps at adequate pressures have been found to be crucial for avoiding defects caused by either excessive outgassing or incomplete degassing. The evaporative mass loss during the SynchroFreeze procedure is characterized and thermal gradients during nucleation for several model systems with concentrations in the 50–400 mg/mL range are analyzed. The technology results in a measurable mass loss that may be relevant for low fill volume formulations. Thermal data show a pronounced temperature gradient throughout the entire product solution during nucleation by vacuum-induced surface freezing. The formulation composition, concentration, and shelf temperature have been shown to influence this temperature gradient. Reliable nucleation was achieved for sucrose formulations with concentrations up to 200 mg/mL at shelf temperatures minimally below the equilibrium freezing point.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Controlled ice nucleation; Freeze-drying; Lyophilization; Nucleation temperature; Vacuum-induced surface freezing